SOURCE(S) AND CYCLING OF THE NONHYDROLYZABLE ORGANIC FRACTION OF OCEANIC PARTICLES - Hwang J.; Druffel E.R.M.; Eglinton T.I.; Repeta D.J. (My University, 2006)
A major fraction of particulate organic carbon (POC) in the deep ocean remains molecularly uncharacterized. In an effort to determine the chemical characteristics and source(s) of sinking POC, we studied a nonhydrolyzable fraction of sinking POC using 13C NMR (nuclear magnetic resonance) spectroscopy and analytical pyrolysis. 13C NMR spectra and products from analytical pyrolysis of the nonhydrolyzable fraction exhibit a strongly aliphatic character that is distinct from that of bulk POC. The aliphatic nature of this fraction is consistent with its low stable carbon isotope values. We hypothesize that the nonhydrolyzable fraction derives to a significant extent from a refractory component of organisms that selectively accumulates, resulting in its manifestation as a major part of POC sinking to the deep ocean and in underlying sediments.